TABU BAHASA DALAM AKTIVITAS JUAL BELI DI PASAR JONGKE KOTA SURAKARTA - Nurham, Reka; Widyastuti, Chattri Sigit (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to examine the use of taboo words in buying and selling interactions at Jongke Traditional Market, Surakarta City. The research used descriptive qualitative method with data collection technique through listening and speaking method. The data obtained are taboo words used by sellers and buyers in transactions. The focus of this research is the types and causes of the use of taboo words in traditional markets. Based on Timothy Jay's theory of language taboos, which divides language taboos into seven types, this study identifies taboo words that fall into the categories of cursing or swearing, abusive words, insults to sacred things, and vulgarity. The results show that the use of taboo words in buying and selling transactions at Jongke Market is often influenced by emotional factors, criticism or dissatisfaction, as well as social conditions around the market. This research provides a deeper understanding of the dynamics of taboo language use in the social and economic context of traditional markets.